Pelatihan Penggunaan Media dan Evaluasi Pembelajaran Matematika Berbasis Higher Order Thinking Skills di Sekolah Dasar - Prayitno, Sudi; Subarinah, Sri; Novitasari, Dwi; Wahyu Triutami, Tabita (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
The use of media can help teachers to explain abstract mathematical concepts so students can more easily understand the material provided. However, teachers in elementary schools in Cluster IV, Sekarbela subdistrict, have difficulty using mathematics media or teaching aids and HOTS-based evaluation. This is because almost all teachers rarely use mathematics teaching aids in their classroom and they don't have props or they do but don't know how to use it. Therefore, teachers need to be empowered to implement HOTS-based teaching aids and evaluations by providing training. The training methods include discussions and demonstrations in using mathematics teaching aids as well as simulations in the use of HOTS-based teaching aids and evaluation in mathematics learning in the classroom. This service activity was carried out at an elementary school in Sekarbela District, with 18 elementary school teachers participating. Evaluation of activities is carried out by post-test. The results show that the teachers participating in the activity: (1) are enthusiastic and active in participating in the activity, (2) can practice using mathematics and GeoGebra teaching aids well, (3) give a positive response to the usefulness of teaching aids or learning media, and (4) able to describe at least 5 geometric shapes correctly on the post-test given